Paper 27: Return to Sport and Testing following Hip Arthroscopy For FAI in High School and Collegiate Athletes. Issue 7 (30th July 2022) - Leary, Steven; Henrichsen, Jake; Schaver, Andrew; Willey, Michael; Paulson, Amanda; Westermann, Robert
Objectives: Femoroacetabular impingement (FAI) is a known cause of hip pain and dysfunction in young, active patients and can be successfully managed with hip preservation surgery. For athletes with FAI, however, there is inconsistent data regarding the ability to return to competitive sport after surgery and how performance level is impacted. The purpose of this study is to evaluate patient factors contributing to return to sport after hip preservation surgery. Methods: Study Design: Retrospective cohort We retrospectively reviewed patients aged 14 to 44 who underwent hip preservation surgery between December 2018 and May 2021 and who participated in a competitive or recreational sport pre-operatively. All patients underwent formal return-to-sport (RTS) testing between 4 and 6 months after surgery. Patient-reported outcomes (PROs) were obtained at initial RTS testing using the International Knee (Hip) Documentation Committee (IKDC) questionnaire, Hip Outcome Score – Sports Specific Subscale (HOS-SSS), and Hip Return to Sport After Injury (Hip-RSI) scale. Regression analysis was performed to evaluate the relationship between RTS tests, PRO's, BMI, pre- and post-operative alpha angles, and degree of correction. Degree of correction was the difference between pre- and post-operative alpha angles measured on Dunn view hip x-rays. Results: We identified 40 patients, 47 operative hips (34 females, 85%). Three patients (4 hips) were excluded for incomplete testing data. Mean age was 17.73 ± 2.7 years. All patients underwent hip arthroscopy for FAI including one case of single-stage bilateral hip arthroscopy. The most common primary sports were dance (7), softball (6), and basketball (5). Mean alpha angles were 67.15 ± 10.9° pre-operatively and 41.37 ± 4.5° post-operatively. Average time from surgery to first RTS testing was 26.79 ± 6.5 weeks (median 25.1 weeks). Mean HOS-SSS score at initial testing was 85.98 ± 11. Posteromedial (PM) and posterolateral (PL) reach on Y-balance test were significantly associated with HOS-SSS score at initial testing (PM: r=0.54, p<0.001; PL: 0.53, p<0.01). Composite Y-balance score was also significantly associated with HOS-SSS score (r=0.6, p<0.01). All other comparisons between PROs and RTS tests were not significantly associated. Similarly, there were no significant associations between time to initial RTS testing and BMI, pre-operative alpha angle, or degree of correction. Conclusions: Higher Y-balance scores at initial RTS testing are associated with improved PROs and perceived readiness to return to sport. This test can be easily incorporated into an assessment for safe return after FAI surgery; further prospective studies are warranted.